Does gender bias affect outcomes in mitral valve surgery for degenerative mitral regurgitation?. (24th April 2021) - Kandula, Viswajit; Kislitsina, Olga N; Rigolin, Vera H; Thomas, James D; Malaisrie, S Chris; Andrei, Adin-Cristian; Ramesh, Ashvita; Kruse, Jane; Cox, James L; McCarthy, Patrick M
Abstract: : OBJECTIVES: This study was conducted to determine if gender bias explains the worse outcomes in women than in men who undergo mitral valve surgery for degenerative mitral regurgitation. METHODS: Patients who underwent mitral valve surgery for degenerative mitral regurgitation with or without concomitant ablation surgery for atrial fibrillation were identified from the Cardiovascular Research Database of the Clinical Trial Unit of the Bluhm Cardiovascular Institute at Northwestern Memorial Hospital and were defined according to the Society of Thoracic Surgery National Adult Cardiac Surgery Database. Of the 1004 patients (33% female, mean age 62.1 ± 12.4 years; 67% male, mean age 60.1 ± 12.4 years) who met this criteria, propensity score matching was utilized to compare sex-related differences. RESULTS: Propensity score matching of 540 patients (270 females, mean age 61.0 ± 12.2; 270 males, mean age 60.9 ± 12.3) demonstrated that 98% of mitral valve surgery performed in both groups was mitral valve repair and 2% was mitral valve replacement. Preoperative CHA2 DS2 -VASc scores were higher in women and fewer women were discharged directly to their homes. Before surgery, women had smaller left heart chambers, lower cardiac outputs, higher diastolic filling pressures and higher volume responsiveness than men. However, preoperative left ventricular and right ventricular strain values, which are normally higher in women, were similar in the 2 groups, indicating worse global strain in women prior to surgery. CONCLUSIONS: The worse outcomes reported in women compared to men undergoing surgery for degenerative mitral regurgitation are misleading and not based on gender bias except in terms of referral patterns. Men and women who present with the same type and degree of mitral valve disease and similar comorbidities receive the same types of surgical procedures and experience similar postoperative outcomes. Speckle-tracking echocardiography to assess global longitudinal strain of the left and right ventricles should be utilized to monitor for myocardial dysfunction related to chronic mitral regurgitation.